Microbiological assessment of keropok lekor production in Kuala Terengganu and Marang, Malaysia - Hamat H.W.; Lani M.N.; Hamzah Y.; Alias R.; Hassan Z. (Asian Journal of Agriculture and Biology, 2024)
Keropok lekor is a popular Terengganu heritage traditional snack and its microbiological safety is one of the important aspects should be of concern. Thus, the present study was carried out to assess microbiological status of keropok lekor, and its production premises in Kuala Terengganu and Marang. A total of 136 samples were collected randomly from eight premises (in three replicates) comprising of raw materials, food contact surfaces and ready to eat (RTE). All samples were analysed for aerobic plate count (APC), total coliforms (TC) count, Escherichia coli and detection of foodborne pathogens. Results showed that the APC and TC count in raw materials (fish flesh, sago starch, ice, dough and chilli paste) ranged from below the detection limit (> 1.0 log10 CFU/g) to 6.7 log10 CFU/g and 4.6 log10 CFU/g, respectively. While, food contact surfaces have the APC and TC in the range of > 1.0 to 6.4 log10 CFU/cm2 and > 1.0 to 4.1 log10 CFU/cm2, respectively. The food handlers hand swabs had APC and TC counts between 2.2 to 6.4 log10 CFU/cm2 and > 1.0 to 4.4 log10 CFU/cm2, respectively. RTE keropok lekor and dipping sauce contained APC in 1.8 to 5.5 log10 CFU/g and > 1.0 to 5.1 log10 CFU/g range, respectively. TC was detected as unsatisfactory level (< 1.7 lo g10 CFU/g) in three keropok lekor samples. E. coli was found in 10.29% of samples and all of them were non-diarrheagenic serotypes. Two RTE keropok lekor and display containers were contaminated with E. coli. Coagulase positive staphylococci, Salmonella and Vibrio parahaemolyticus were detected in four, two and one samples, respectively, with none of them found to have Vibrio cholerae and Listeria monocytogenes. High prevalence of indicator organisms in food contact surfaces and food handlers hand indicated that hygiene practices were not well implemented. The unsatisfactory levels of presence of APC, TC and E. coli in RTE keropok lekor also described cross contamination due to inadequate hygiene practices after cooking process. 2019 Asian Journal of Agriculture and Biology.